2003
DOI: 10.1097/00001756-200303030-00026
|View full text |Cite
|
Sign up to set email alerts
|

Age-related brain parenchymal fraction is significantly decreased in young multiple sclerosis patients: a quantitative MRI study

Abstract: The extent of brain atrophy was determined in 33 patients with multiple sclerosis (MS) and in 60 healthy subjects (21-76 years) by calculating brain parenchymal fractions (BPF, the ratio of brain parenchymal to intracranial volume) from 3D MRI. Within the normal data base, subjects at higher ages showed significantly lower BPF values. In younger MS patients, BPF was significantly decreased compared with age-matched controls (20-29 years, p= 0.0022; 30-39 years, =p 0.0001; 40-49 years,p = 0.0444) and was signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
30
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 0 publications
6
30
0
Order By: Relevance
“…We observed BPF to decrease significantly in the subgroup of patients that showed relapses under therapy with GA (study onset vs. 3 years of follow-up), even though no significant difference of BPF between patients with or without relapses was detectable over follow-up. This observation is in line with previous studies that suggested brain atrophy to occur early on in the disease and to be present even though patients may show only mild progression of clinical disability [16,34,35]. No significant progression of T 2 lesion load over follow-up was observed.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We observed BPF to decrease significantly in the subgroup of patients that showed relapses under therapy with GA (study onset vs. 3 years of follow-up), even though no significant difference of BPF between patients with or without relapses was detectable over follow-up. This observation is in line with previous studies that suggested brain atrophy to occur early on in the disease and to be present even though patients may show only mild progression of clinical disability [16,34,35]. No significant progression of T 2 lesion load over follow-up was observed.…”
Section: Discussionsupporting
confidence: 92%
“…For lesion identification, two different T 2 -weighted turbo spin echo sequences were collected. For further data processing, the algorithms implemented in Statistical Parametric Mapping software (SPM, Department of Imaging Neuroscience Group, London, UK) were used as previously described [16,20]. Data were normalized to the Montreal Neurological Institute standard template provided with SPM.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 Higher Expanded Disability Status Scale scores and longer disease duration both correlated with a higher degree of atrophy, which has also been reported in earlier studies. 3,4 Although caution should be taken in comparing BPF measurements between studies that used different methods, 25,26 it is our interpretation that the strong agreement with literature values indicates the validity of using SyMap for determination of BPF.…”
Section: Comparison With Bpf Values From Previous Studiesmentioning
confidence: 61%
“…[2][3][4][5][6] Calculation of BPF requires differentiation between brain parenchyma and CSF. Several different techniques based on MR imaging, manual as well as semiautomatic and automatic, can be used to accomplish this.…”
mentioning
confidence: 99%